Analytical studies of the penetration dynamics of starting forced plume - Toh, Vincent Woon Sen. (2009)
Plumes are a formed when a fluid discharges into another fluid of a different density. These are common phenomenon and can be seen as hot ashes being released during a volcanic eruption. The study of mixing and entrainment of plumes is therefore of environmental focus. While the far-field penetration of the plume has been properly documented, the near-field is yet to be understood. Therefore, near-field studies for the penetration dynamics of plumes will be the focus of this project study.